The Future of Electric Vehicles: Infrastructure Challenges, Battery Technology, and Automotive Industry Developments - Anggia Faradina (Technologia Journal, 2024)
This article is based on a literature review that includes various academic studies, industry reports, and trend analysis related to the development of electric vehicles. This method aims to provide a comprehensive overview of the challenges and opportunities in the adoption of electric vehicles, especially in the aspects of infrastructure, battery technology, and vehicle production and distribution. By collecting and analyzing data from various reliable sources, this article can present accurate and relevant information on electric vehicle trends at the global and regional levels. The results of the study show that while electric vehicles offer environmentally friendly solutions and better energy efficiency than fossil fuel vehicles, there are various challenges that need to be overcome. These include limited charging infrastructure, high battery production costs, and the need for regulatory policies that support the transition to electric vehicles. This article also discusses potential solutions through technological innovation, cross-sector collaboration, and sustainable investment in electric vehicle development. With the right strategy, electric vehicles have the potential to become the main choice in a more sustainable transportation future.